Immunohistochemical positive regulatory domain member 10 expression in soft tissue sarcomas - Mistik, Ozge; Sayar, Hamide (Polish Journal of Pathology, 2022)
Positive regulatory domain member (PRDM) proteins play a critical role in the transmission of signals that control cell proliferation and differentiation, and neoplastic transformation. Positive regulatory domain member 10 (tristanin) is a poorly studied member of PRDM protein family. Gene fusion transcripts containing PRDM10 were recently identified in low-grade undifferentiated pleomorphic sarcomas (UPS), and associated with pleomorphic morphology and low mitotic index. The aim of this study was to investigate the immunohistochemical staining of PRDM10 in a larger sample of soft tissue sarcomas. Therefore, the study included 118 soft tissue sarcomas from different classes, and PRDM10 antibody was applied to all of them. Immuno-histochemically, staining was observed in 22 (19%) cases, while 96 (81%) showed no staining. When PRDM10 expression was compared with clinico-pathological features, there was a statistically significant correlation between PRDM10 expression and myxoid changes, multi-nucleated giant cells, and surgical margin (p = 0.017, p = 0.034, p = 0.032, respectively). No statistically significant association was found between PRDM10 expression and other parameters. Based on the obtained data, it can be said that PRDM10-positive-stained tumors (tumors with PDRM10 expression) are mostly myxoid, containing multi-nucleated giant cells, and can be removed with well-circumscribed margins.